2018
DOI: 10.2319/120317-825
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between 3D dentofacial photogrammetry measurements and traditional cephalometric measurements

Abstract: Objectives: To determine the relationship between traditional cephalometric measurements and corresponding nonradiographic three-dimensional (3D) photogrammetry measurements. Materials and Methods: This was a cross-sectional study of 20 orthodontic patients (10 male and 10 female) who received lateral cephalometric radiographs and 3D dentofacial photogrammetric records with each subject serving as his or her own control for a total sample size of 40 images (20 per method). A 3D analysis that resembled a tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Studies on related topics in various fields have also been gaining more popularity. 3,[11][12][13][14] Although three-dimensional images have gained popularity these days, [15][16][17][18][19] two-dimensional cephalometric analysis is still a vital tool in orthodontic diagnosis and treatment planning since it provides information regarding a patient's skeletal and soft tissue. Currently, computer-assisted cephalometric analysis eliminates human-induced mechanical errors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on related topics in various fields have also been gaining more popularity. 3,[11][12][13][14] Although three-dimensional images have gained popularity these days, [15][16][17][18][19] two-dimensional cephalometric analysis is still a vital tool in orthodontic diagnosis and treatment planning since it provides information regarding a patient's skeletal and soft tissue. Currently, computer-assisted cephalometric analysis eliminates human-induced mechanical errors.…”
Section: Discussionmentioning
confidence: 99%
“…All rights reserved Beam Computed tomography (CBCT) scans 14 or to cut down the application of lateral cephalograms. 15 Although several methods have been proposed to record NHP in 3D, 11 only one study 16 has reported on the stability of NHP in all three dimensions. Additionally, one study has reported the stability of NHP for rotations around the x -and z-axes.…”
Section: Accepted Articlementioning
confidence: 99%
“…The future goal might be the application of this method to threedimensional (3D) data. While 3D photogrammetry and 3D cephalometrics look promising in the near future, 21,[24][25][26] one of the major challenges might be that a 3D prediction algorithm will demand more massive data than would be required in a two-dimensional situation. Going to 3D would present even more of a burden on measurement and computational resources.…”
Section: Discussionmentioning
confidence: 99%